No time to waste for wasted children in Bihar: time to reset - Saurabh, Kumar; Jaiswal, A. K.; Tiwari, A. K. (International Journal of Contemporary Pediatrics, 2024)
Background: Severe acute malnutrition (SAM) with severe wasting remains a major killer of children. In Bihar, 48% of children are stunted, 21 % are wasted, and 7% are severely wasted. Even during the first six months of life, 31% are wasted. The objective of this study was to study wasting trends and contributing factors responsible for changes in Bihar among children 0-5 years. Methods: This cross-sectional study was done using a data of NFHS-5 survey in Bihar (N=35,834) conducted in all 38 districts of the state from July, 2019 to February, 2020. The Bihar NFHS-5 report and factsheets, including NFHS-4 data, were downloaded and converted to excel to enable data visualization and trend analysis. The outcome variable Wasting was measured using NFHS-5 relevant questionnaires given under nutrition category. We analyzed trends between NFHS-5 and NFHS-4 Bihar data for severe wasting/wasting, determinants, and coverage of interventions. Results: The prevalence of severe wasting has increased from 7% to 8.8%, while wasting increased from 20.8% to 22.9% (NFHS-5). The severe wasting and wasting has reversed or worsened in 27 districts. There is a mixed picture of infant feeding- early initiation of breastfeeding worsening and some improvements in exclusive breastfeeding and timely introduction of complementary feeding. Consistent improvement across districts for underlying determinants, but slight, in women’s education, teenage pregnancy, and marriage before 18 years. Conclusions: Need to invest in improving maternal determinants-age at marriage, education, ANC coverage, and teenage pregnancy. It is imperative to focus on preventing, identifying, and treating wasting.